PEMUTUSAN HUBUNGAN KERJA AKIBAT KEADAAAN MEMAKSA (FORCE MAJEURE) DI PT. CIMB NIAGA AUTO FINANCE CABANG SURABAYA DITINJAU DARI UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Christian P.W. Hutasoit; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Economics is the most influential aspect in society. Economics becomes the first consideration in Determining policy. Indonesia is a country of law. The characteristic of state law is giving the protection of Human Rights. The purpose of this study was to research the economic crisis can be used as a reason for the employment termination due to force majeure in Undang-Undang No. 13 Year 2003 about Manpower and knowing the implementation of the Employment Termination in PT.CIMB. This research was a sociological study. The research location was at PT. CIMB Niaga Auto Finance Branch Surabaya. Legal protection as a description of the function of law is a concept where the law can give an assurance, benefit and peace. PT. CIMB Niaga Auto Finance Branch of Surabaya had been carrying out legal protection to workers affected by employment termination due to force majeure. The reasearch found that Law No. 13 of 2003 about Manpower need a revision especially about the economic crisis can be included as a reason for termination of employment. Hopefully PT. CIMB Niaga Auto Finance Branch can continue to run their business in order to continue to fulfill the needs of the community.Key Words: Force Majeure - Legal Protection - PT. CIMB Niaga Auto Finance Branch Surabaya